2022
DOI: 10.21037/jtd-22-585
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-butylphthalide attenuates myocardial ischemia reperfusion injury by suppressing oxidative stress and regulating cardiac mitophagy via the PINK1/Parkin pathway in rats

Abstract: Background: Acute myocardial infarction (AMI) is one of the leading causes of mortality worldwide.Undesirable myocardial damage may occur during reperfusion of the ischemic myocardium, and this is known as "ischemic reperfusion injury" (IRI). Currently, there are few effective drugs to alleviate IRI. Dl-3-n-butylphthalide (NBP) is recommended for the treatment of acute ischemic stroke in China. This study investigated the effects of NBP on IRI and its underlying mechanisms. Methods:The left anterior descending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…42 A previous study reported that NBP could attenuate myocardial ischemia-reperfusion injury by inhibiting oxidative stress. 43 In addition, it has also been reported that NBP alleviated secondary brain injury by promoting neovascularization and vascular remodeling during recovery. 43 Given NBP's favorable properties of reducing oxidative stress levels and enhancing angiogenesis, we hypothesize that NBP may also prove beneficial in rapid TES healing.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 A previous study reported that NBP could attenuate myocardial ischemia-reperfusion injury by inhibiting oxidative stress. 43 In addition, it has also been reported that NBP alleviated secondary brain injury by promoting neovascularization and vascular remodeling during recovery. 43 Given NBP's favorable properties of reducing oxidative stress levels and enhancing angiogenesis, we hypothesize that NBP may also prove beneficial in rapid TES healing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…43 In addition, it has also been reported that NBP alleviated secondary brain injury by promoting neovascularization and vascular remodeling during recovery. 43 Given NBP's favorable properties of reducing oxidative stress levels and enhancing angiogenesis, we hypothesize that NBP may also prove beneficial in rapid TES healing. Building on this hypothesis, NBP and BP nanoflakes were both encapsulated in a chitosan (CS) hydrogel to determine whether their incorporation could be used for enhanced osteogenesis and angiogenesis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DL-3-n-butylphthalide (NBP), the first class I novel drug, which has been approved for the treatment of acute ischemia stroke in China since 2002 [9][10][11]. On account of the neuroprotective properties of NBP by eliminating free radicals, restoring mitochondrial function, reducing neuroinflammation and alleviating neuronal apoptosis, its therapeutic spectrum has expanded to various neurodegenerative diseases, such as Alzheimer disease (AD), Amyotrophic Laternal Sclerosis (ALS) and PD [12][13][14][15][16]. To date, many studies have clarified the benefit role of NBP in PD both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…After coronary recanalization in the infarcted area, arrhythmia, decline of cardiac function, and sudden cardiac death often occur clinically. The pathogenesis of MIRI is complex, involving oxidative damage ( 3 , 4 ), inflammatory response ( 5 , 6 ), calcium overload ( 7 , 8 ), and other processes. Many mechanisms of MIRI are unclear, especially the role of the immune microenvironment in MIRI remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%